Survei Tingkat Ketepatan Passing dan Koordinasi Mata-Kaki pada Atlet Sepakbola SSB Jatayu FC Watukelir Kabupaten Sukoharjo Tahun 2025 - Zilda Mahayudi; Kodrad Budiyono; Pipit Fitria Yulianto (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the level of eye-foot coordination and passing accuracy among 30 soccer athletes of SSB Jatayu FC Watukelir, Sukoharjo Regency, in 2025. This research employed a quantitative descriptive approach using a purposive sampling technique. Data were collected through observation of training processes and standardized tests measuring passing ability and eye-foot coordination. The collected data were analyzed using descriptive percentage techniques. The findings revealed that: (1) The athletes' passing ability was generally categorized as